Food sovereignty in a new lens: Synergies between new economic sociology and resilience as a possible way (Research, Society and Development, 2021)
This article seeks to contribute to the debate around food sovereignty in contemporary times from the perspective of the New Economic Sociology. These analytical tools are used here to support the interpretation of new forms of economic integration, as well as traditional ones, which are marginalized by the process of modernization in a context of society that constantly produces crises and risks. In this sense, forms of economic integration based on categories such as solidarity, reciprocity, cooperation and trust can corroborate the building of resilience that contributes to the constitution of food sovereignty.